Effect of Combination of Gonadotropin Releasing Hormone (GnRH) and Vitamin E-Selenium on the Success Rate of Artificial Insemination of Repeat Breeding Beef Cattle - Rosalia, Vika; Cahyani, Annisa Putri; Widodo, Agus Tri (Jurnal Penelitian Peternakan Terpadu, 2024)
This research was conducted to determine the effect of the use of Gonadotropin Releasing Hormone (GnRH) and Vitamin E-Selenium on cows experiencing reproductive disorders in the form of repeat breeding. This study used 20 repeat breeder beef cattle which were divided into 4 groups and 3 treatments and 5 replicates: P0 (control), P1 (AI+GnRH 5 ml), P2 (AI+Vitamin E-Selenium 20 ml), P3 (AI+GnRH 5 ml+Vitamin E-Selenium 20 ml). The NRR and CR data obtained were analyzed using the Cochran's Q Test, which if the test showed a real effect, the Pairwaise Comparison test would be continued. The results of the study stated that there was no real effect of the combination of GnRH hormone and Vitamin E-Selenium on the success rate of Artificial Insemination in repeat breeding beef cattle (P>0.05). In the P3 treatment, the pregnancy rate was 80% and P1 also produced the same pregnancy rate, which was 80%. This figure is higher when compared to the results of P0 which is 0% and P2 which is 40%. Based on the four groups and 3 treatments, it can be seen that the addition of a combination of GnRH and Vitamin E-Selenium injection has a higher influence in terms of the percentage of pregnancy, Non Return Rate and Conception Rate produced. This is because GnRH is able to induce a pre-ovulation LH surge. Increased LH concentrations promote oocyte maturation, induce ovulation and can improve the function of the corpus luteum. Abstracts must be written in Indonesian Language.